Endophytic Fungus, Clerodendrum speciosissimum Jacob-Makoy (Lamiaceae) in West Lombok - Nadia, Ahsanu; Harisandi, Hadian; Yoginanta, Muhammad Daffa; Mulyaningsih, Tri (Jurnal Biologi Tropis, 2025)
Clerodendrum speciosissimum in Indonesia is known as the pagoda plant, which is used as a traditional medicinal plant. Organisms that are in plant tissue for all or part of their life cycle and do not cause infection are called endophytes, which include fungi. Endophytes are known as producers of chemicals in plants. Endophytic fungi are also used as producers of antibacterials, antifungals, and antioxidants. The purpose of this study was to isolate and identify endophytic fungi found in pagoda plant tissue and to determine the presence of endophytic fungi, using the patch method, 12 isolates were successfully isolated and identified into four genera, namely Aspergillus, Penicillium, Phytium, and Phytophthora. The presence of endophytic fungi can be detected in the cortex and pith tissue of the leaf midrib, while in the stem, endophytic fungi are found in the cortex, phloem, and pith tissues.